Treatment of uncertainty in determining the UK's path to Net Zero - Joffe, David (Frontiers in Climate, 2023)
The Climate Change Committee (CCC) recommended the UK's 2050 Net Zero target in 2019 and then the emissions pathway to this as part of its advice on the Sixth Carbon Budget at the end of 2020. As part of this, the CCC's analysis included development of five pathways to Net Zero, incorporating a number of judgements and framings regarding uncertainty and decision points, to highlight key choices for Government and wider society on the path to Net Zero. This paper explores how the analysis, and its presentation, framed these choices and uncertainties, in order to highlight where decisions are required and what the trade-offs and potential contingency options might be. It concludes with reflections on the effectiveness of this approach and on the future challenges on decision-making and uncertainty towards Net Zero. This is a provisional file, not the final typeset articleThe challenge of addressing uncertainty in the Sixth Carbon Budget adviceThe underlying requirement of the December 2020 advice on the level of CB6 was to advise on the level of the carbon budget for the period 2033-37, accompanied by a range of accompanying recommendations (e.g. on treatment of emissions from international aviation and shipping in the carbon budget). The Government is then required to legislate a level for the carbon budget, either in line with the CCC's advice, orif differentsetting out why the level differs from that recommended by the CCC.